Avaliação de quatro métodos de produção de geleia real e rainhas de Apis mellifera no estado do Ceará - Silveira Neto, Antonio Abreu da (2011)
The experiment was conducted at the Faculty Technology FATEC - Wilderness Center in the city of Quixeramobim - CE, and was divided into two stages. The goal of the first phase conducted from February to April 2010 was to evaluate the influence of rearing for royal jelly production and larval weight of Apis mellifera transferred. The second step was evaluated important aspects in the production of queens as the influence of the growing weight of emerging queens, their morphometric characteristics, and dry weight of their ovaries, being conducted from October 2010 to February 2011. Two apiaries were used, a small apiary that received colonies the four models used in the study: Doolittle, Orfanos with a hive, Mini-hive and Chinese, and others to support the same with 25 colonies. Colonies each received a door-frame dome domes containing 32 plastic artificial color blue, 16 in the top batten and the bottom 16. Data collection was done in two days of the week in the first phase of the trial and three days in the second stage. In the first phase, 448 transfers were performed for each larval rearing, a total of 1792 larvae transferred. In the second phase were produced in 263 colonies all the queens. The results showed no significant difference (p > 0,05) in acceptability and weight of larvae transferred, as well as in royal jelly production by growing, but there was a positive correlation between these parameters. There were also the same statistical differences and correlations for the weight of the ovaries and dry matter. The production of royal jelly dome, the weight of the queen to emerge and their morphometric measurements showed statistically significant differences (p <0.05) and Doolittle hive stood out positively on royal jelly production, while Chinese demonstrated the growing queens producing smaller and lighter. We conclude that hive Doolittle are more suitable for the production of royal jelly, since it utilizes a number higher than the domes used in this study, and re-create that Mini-hive in the production of queens.